P243Glucose metabolism and blood pressure control status in professional hypertension clinics in China. (15th July 2014) - Wang, H; Sun, N; Huo, Y
Abstract: Objective: To investigate the glucose metabolism status, cardiovascular risk factors distribution and blood pressure control rate in patients who were diagnosed and treated in the professional hypertension clinics in China. Methods: A cross-sectional survey was conducted to 32004 patients in 127 professional hypertension clinics across the country. The questionnaire included the history of associated diseases and its treatment conditions. Physical examination and biochemical tests were also performed at the same time. Results: The mean blood pressure was 150.34/92.21mmHg in all the patients. 3424 patients (10.7%) had never taken any anti-hypertension medicine. Among patients treated with anti-hypertension drugs, 19818 cases received mono-therapy(69.3%) and 8762 cases received combination therapy(30.7%). The most frequently used drug was renin-angiotensin system inhibitors, followed by calcium-channel blockers. About 15.6% patients had taken fixed compound preparations. - The overall blood pressure control rate (<140/90 mmHg ) was 26.8%, which was 27.7%, 30.0%, 25.4% and 21.3% in patients complicated with coronary heart disease, diabetes mellitus, kidney diseases and cerebral stroke respectively. - About 70.3% hypertensive patients had abnormal glucose metabolism whose mean GHbA1c was 7.84% which was much higher than 7.0%, the target value defined by ADA, even among them, 20.2% had not taken any anti-diabetic drugs. - Low-risk and medium-risk patients accounted for 16%, 48.0% of high-risk and 36.0% of very high risk. About half of all patients had different target organ damages and about 49% of them had associated with clinical complications. Conclusions: Hypertension complicated with abnormal glucose metabolism was widespread, more target organ damages and clinical diseases exist in these patients, but less than 30% of them had reached the target blood pressure. Low proportion of the combination therapy was one of the reasons of low blood pressure control rate. This showed that the effective management of blood pressure is inevitable.